The Representation of Reunion 212 in Indonesian Online Media - Ibnus, Nizar (NOTION: Journal of Linguistics, Literature, and Culture, 2019)
Reunion 212 which is the action of a series of previous actions was reported by many media in Indonesia. Each media portrays the action differently. This critical discourse analysis attempts to uncover the practice of power in Indonesian online media regarding the rally. Data were analyzed using van Dijk discourse analysis approach which consisted of text analysis, social cognition, and social context. The findings reveal that CNN Indonesia.com is more concerned about the adverse effects of the action and the purpose of the action which is considered politically charged, while Republika Online brings more humanist themes but also does not deny the potential political purpose behind the action. The themes are supported by certain lexical and discourse strategies. Moreover, the power practice is more visible in CNN Indonesia.com which attempts to convince readers that the action is bad and orientates itself more toward political purposes. While the news from Republika Online is more informative and only contains the good side of the action.